Proceedings of 12th World Congress on Genetics Applied to Livestock Production (WCGALP) 2022
DOI: 10.3920/978-90-8686-940-4_56
|View full text |Cite
|
Sign up to set email alerts
|

56. Towards the characterisation of animal robustness by dynamic energy allocation indicators in fattening pigs

Abstract: The objectives of this study were to investigate the possibility of characterising animal robustness by using indicators based on the dynamics of energy allocation of the animal and to determine their genetic parameters. A total of 2 140 pigs, from the Piétrain NN Français line, were raised at the AXIOM boar testing station. This farm was equipped with automatic feeding system, recording individual weight and feed intake at each visit. We used a dynamic linear regression model to characterize the evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The trait α t , which describes the allocation of net energy to growth during the fattening period, had moderate heritabilities, in the same range as those estimated for FCR or RFI. In a previous study [48], we considered the average estimate of α t during the evaluated period and not the daily estimates, and obtained a lower heritability (0.16 ± 0.05) but this was based on a different dataset. For RFI, David et al [49] reported heritabilities ranging from 0.19 ± 0.06 to 0.28 ± 0.06, using an RR model for weekly estimates of RFI over 10 weeks in pigs.…”
Section: Estimation Of the Genetic Variance Of The Allocation Coeffic...mentioning
confidence: 95%
“…The trait α t , which describes the allocation of net energy to growth during the fattening period, had moderate heritabilities, in the same range as those estimated for FCR or RFI. In a previous study [48], we considered the average estimate of α t during the evaluated period and not the daily estimates, and obtained a lower heritability (0.16 ± 0.05) but this was based on a different dataset. For RFI, David et al [49] reported heritabilities ranging from 0.19 ± 0.06 to 0.28 ± 0.06, using an RR model for weekly estimates of RFI over 10 weeks in pigs.…”
Section: Estimation Of the Genetic Variance Of The Allocation Coeffic...mentioning
confidence: 95%